Efeito imunomodulador de nanopartículas usadas na nanomedicina] [Efecto inmunomodulador de nanoparticulas usadas en nanomedicina (2023)
Nanoparticles (NP) are structures with a size on the nanometer scale (1 × 10-9 m). Due to their characteristics, their potential use in the fields of biotechnology and biomedicine has grown in recent years with a wide range of applications, such as diagnosis, therapy and regenerative medicine. The immune system is responsible for defending the body against pathogenic organisms and other foreign agents, such as NP, which can be recognized by such system, interact with it and modulate its function inducing immunostimulatory or immunosuppressive effects. The latter could be used as anti-inflammatory therapeutic agents or to treat autoimmune diseases, and those that activate the immune system, as adjuvants in vaccination or enhancers of the immune response in cancer and other human diseases. However, their use in nanomedicine should be submitted to preliminary tests to determine their effects on the immune response before being applied to biological systems. For this reason it is important to know their composition, size and surface characteristics, as well as other physicochemical properties, directly involved in the effects on the immune system. We present an overview about the relationship between the physicochemical characteristics of NP candidates to be used in the biomedical and biotechnological fields and their immunomodulatory activity. © 2016, Universidad de Antioquia. All rights reserved.